Did the Digital Push Last? E-Commerce and Rural Agricultural Earnings in Indonesia During and After COVID-19, Evidence from Sakernas - Ruslan, Kadir; Sukma, Weni Lidya (Politeknik Statistika STIS, 2025)
This paper examines the impact of e-commerce adoption on earnings and incomedistribution among rural agricultural employers in Indonesia, both during and after the COVID19 pandemic. Using microdata from the National Labour Force Survey/Sakernas (2018–2024)and applying probit, OLS, Propensity Score Matching, and quantile regression models, weidentify the determinants of adoption and its impact on earnings. Adoption was strongly drivenby education, training, and enterprise characteristics, while older age and reliance on unpaidhousehold labor constrained uptake. Results show that e-commerce adopters earned substantiallyhigher than non-adopters (more than 30 percent) both during and after the pandemic, confirmingsustained income gains beyond the crisis. Quantile regressions reveal that the lowest-incomeemployers benefited most, with earnings gains exceeding 50 percent at the bottom quantileduring the pandemic. Although relative advantages shifted toward higher earners after thepandemic, large and significant effects remained for the lowest-income groups. These findingsindicate that e-commerce not only enhances market access but also contributes to improvingincome distribution. Policy interventions to strengthen digital literacy, rural infrastructure, andfinancial access are essential to preserve its inclusive role and ensure that vulnerable agriculturalemployers continue to benefit disproportionately.